THE CONCEPT OF POSITION IN THE LABOR FUNCTION - S. Titor (Вестник университета)
Protection of workers’ labor rights is one of the priority directions of the state social policy. But often the employee is faced with a discrepancy in legislation and law enforcement practices. Theoretical aspects of labour law are constantly being improved. The concept of «position» is found in administrative law, in state and municipal legislation. But it is somewhat dierent from his understanding of labor law. However, from his correct understanding sometimes depends on the preservation of labor relations with the employee. Today it is important to consider the concept of positions in the labor function.